THE RELATIONSHIP BETWEEN OBESITY AND THE HABIT OF CONSUMING SUGAR-SWEETENED BEVERAGES ON FASTING BLOOD GLUCOSE LEVELS IN ADULTHOOD (Case: Puskemas Tanjung Morawa) - Siti Mirhalina Hasibuan; Nada Rizki Hanifah (Jurnal Kesehatan, 2023)
According to WHO data (2010) sufferers of diseases related to blood glucose levels in the world estimated at 171,000,000 world population. Especially in developing countries such as Indonesia with the number of sufferers increasing by around 85% at the age of over 25 years while in Southeast Asian countries, the incidence rate is 4.5 million people. Blood glucose levels can be checked when the patient is fasting or it could be when the patient comes to check. A sugar-sweetened beverage is a type of drink that is added sugar during the production process. Sugars that are commonly used are white sugar, brown sugar, corn sugar, and honey. This study aims to determine the relationship between obesity and the habit of consuming Sugar-Sweetened Beverages on fasting blood glucose levels in adults at the Tanjung Morawa health center. This research method uses a case-control design at Tanjung Morawa Health Center. The results of the study were found in the Mann-Whitney test to have a value of p = 0.02 where the value of p < 0.05 so that there is a relationship between obesity and fasting blood glucose levels in adulthood at the Tanjung Morawa health center. The results of the Kruskal Wallis test have a value of p = 0.01 where the value of p < 0.05 so that there is a relationship between the habit of consuming Sugar-Sweetened Beverages to fasting blood glucose levels in adulthood at the Tanjung Morawa health center.